Game Edukatif Make a Match: Solusi Inovatif untuk Meningkatkan Hasil Belajar Matematika di Sekolah Dasar - Surya Widyasari; Zulqoidi R. Habibie; Elvima Nofrianni (Master of Action Research in Mathematics Classroom, 2025)
This study is driven by the learning process that does not yet align with the requirements of the Independent Curriculum, along with students' low academic achievement. The study is centered around the following research concern "How to improve the process and results of learning mathematics through the application of the make a match model assisted by card installation media at stage B (Class IV) SDN 094 / VIII Giriwinangun?" This type of research is This investigation followed the principles of Classroom Action Research and was performed in March 2025 at SDN 094 / VIII Giriwinangun in semester II. Class IV consisted of 15 students, including 10 boys and 5 girls. Relevant data was obtained gathered With the application of observation and testing methods. The findings revealed that the teacher's learning process adopting the make a match technique assisted with card installation media during the first cycle, the percentage was reaching 80.46%. Furthermore, there was a growth in Cycle II, reflected by a percentage of 82.81%. Students during the learning process the application of the Make a Match strategy supported by card-matching media in Cycle I achieved 46.7%. Furthermore, by Cycle II, it had reached 93.3%. Assessment of student academic results achieved using the Make a Match strategy aided by card-matching media in cycle I reached 60%. While in cycle II student learning outcomes reached 80%. As indicated by the conclusions drawn from this investigation, It may be inferred that implementing the Make a Match model with the support of card pairing media enhances both the learning process and outcomes of fourth-grade students at SDN 094/VIII Giriwinangun.